Analisis Prinsip Good Corporate Governance dalam Regulasi Hukum Perusahaan - Zahada Sabhira, Salma; Umar Fadhilah, Muhammad (UM Purwokerto Press, 2024)
Good Corporate Governance in companies in Indonesia or commonly known by the short term (GCG) is a governance framework that includes ethical rules and norms to protect the integrity, especially in this writing, of companies to improve their performance. The principles of Good Corporate Governance (GCG) emphasize fundamental principles that must be implemented to increase company effectiveness and compliance with company legal regulations. Good corporate governance (GCG) is an important concept in regulating company behavior to ensure transparency, accountability, fairness and compliance with the law. In corporate legal regulations, GCG principles are the basis for building a framework that ensures effective management, protection of shareholder interests and appropriate risk management. Through in-depth analysis of GCG principles, company legal regulations can be strengthened to create a healthy and sustainable business environment. However, there are obstacles to its implementation, including legal, cultural, political and business environments. Despite being a pressure, GCG is recognized as an opportunity to improve quality and sustainability in business efforts. The main challenge involves changing the company culture towards solid and transparent leadership. Steps to develop GCG require integrated awareness and good relationships between various stakeholders in the company. GCG principles, such as transparency, accountability, responsibility, independence and equality, are needed to ensure fair protection and interests for all parties involved in the company.